INDIVIDUAL DIFFERENCES IN HOW LANGUAGE LEARNERS PURSUE GOALS: REGULATORY MODE PERSPECTIVE. Issue 3 (12th July 2022) - Teimouri, Yasser; Papi, Mostafa; Tahmouresi, Somayeh
Abstract: In two studies, we examined two functional dimensions of L2 learners' self-regulation toward their motivational goals: assessment and locomotion. The assessment constitutes the aspect of self-regulation concerned with critically evaluating the relative quality of L2 states and goals and the means to achieve them. The locomotion mode constitutes the aspect of self-regulation concerned with uninterrupted movement from state to state toward L2 goals. We developed two scales to measure L2 self-regulatory modes. We also examined how L2 learners' regulatory modes were associated with their emotional experiences, motivation, and language proficiency. Psychometric work attested to the reliability and validity of the two scales. Moreover, regression analyses revealed that each L2 self-regulatory mode has distinct emotional, motivational, and linguistic emphases. Finally, cluster analyses suggested that both L2 self-regulatory modes should work together for optimal L2 learning outcomes.